Biodiesel synthesis using natural solid catalyst derived from biomass waste — A review - Chua, Song Yuan; Periasamy, Loshinie; Goh, Celine; Tan, Yie Hua; Mujawar, Mubarak; Kansedo, Jibrail; Khalid, M.; Walvekar, R.; Abdullah, E.C. (2020)
© 2019 The Korean Society of Industrial and Engineering Chemistry Biodiesel serves as an ideal candidate for alternative fuel as it is made from renewable source with lower pollutant emission. However, current biodiesel production has several issues such as unrecoverable catalyst, expensive separation stage and high wastewater generation due to the use of homogeneous catalyst. Currently, there are several pathways to produce biodiesel without the problems stated above such as supercritical condition transesterification and enzymatic catalyst. However, the economic feasibility for both methods serve as a major hindrance due to extremely high pressure and pressure, expensive synthetic cost of enzyme, which lead to higher operation cost. At the present, heterogeneous catalyst is the alternative, especially heterogeneous catalyst derived from natural resources such as waste biomass are currently being extensively researched with promising results. Thus, this paper illustrates the comprehensive research of biodiesel synthesis and assesses the latest breakthroughs involved in the use of catalysts derived from waste biomass. Furthermore, an amalgam of experimental data obtained from similar literature has been thoroughly reviewed to provide a better framework to produce biodiesel. Apart from that, this study aims to alleviate problems associated with heterogeneous catalyst separation and enhance the economic viability of the industry, thus, sustaining the environment while meeting energy demands.